Modelling the risk of airborne infectious disease using exhaled air. (7th May 2015) - Issarow, Chacha M.; Mulder, Nicola; Wood, Robin
Abstract: In this paper we develop and demonstrate a flexible mathematical model that predicts the risk of airborne infectious diseases, such as tuberculosis under steady state and non-steady state conditions by monitoring exhaled air by infectors in a confined space. In the development of this model, we used the rebreathed air accumulation rate concept to directly determine the average volume fraction of exhaled air in a given space. From a biological point of view, exhaled air by infectors contains airborne infectious particles that cause airborne infectious diseases such as tuberculosis in confined spaces. Since not all infectious particles can reach the target infection site, we took into account that the infectious particles that commence the infection are determined by respiratory deposition fraction, which is the probability of each infectious particle reaching the target infection site of the respiratory tracts and causing infection. Furthermore, we compute the quantity of carbon dioxide as a marker of exhaled air, which can be inhaled in the room with high likelihood of causing airborne infectious disease given the presence of infectors. We demonstrated mathematically and schematically the correlation between TB transmission probability and airborne infectious particle generation rate, ventilation rate, average volume fraction of exhaled air, TB prevalence and duration of exposure to infectors in a confined space. Abstract : Highlights: Quantified rebreathed air with high airborne infectious diseases transmission risk. We developed a mathematical model that predicts the risk of airborne infectious diseases. The model uses deposition fraction, particle survival and mortality rates but not quanta. The model works in multiple environments obeying infectious particles threshold level. The model matches individual and environment without limitations of uniformly mixed air.